Combating Corruption in the Public Sector: International Legal Standards and their Implementation in the Legislation of Ukraine - Vaitsekhovska, Oksana; Iakymchuk, Nataliia; Shchokin, Yuriу; Vorotina, Nataliia; Korchak, Nataliia (ASOC ECONOMIA APLICADADC JUAN RAMON JIMENEZ, 43, MADRID 28036, SPAIN, 2021)
Nowadays, one of the reasons for the ineffective fight against corruption in the budget system is certain discrepancies and inconsistencies between the legal components of the mechanism for countering this antisocial phenomenon. The lack of a clear definition of the limits of competence of participants in the budget process, discretionary powers in the distribution and expenditure of budget funds, conflicts in budget legislation, and the lack of real competition in the field of public procurement clearly form the main corruption risks for all participants in these legal relations. The purpose of the study was to analyse the international legal mechanisms for combating corruption and find ways to implement them in Ukrainian legislation. Enforcement of corruption crimes should be further strengthened at all levels. National Anti-Corruption Bureau of Ukraine should be provided with necessary resources, including more analytical capacity and better access to outside official experts. Methodological guidelines on most challenging and complicated issues need to be developed. International cooperation in corruption cases should be continued and further improved. And finally, court practice should be followed up to see what challenges will emerge at the stage of adjudication.
Keywords: Corruption; National security; European standards; Mechanism Public funds